The Effect of Institutional Factors and their Weight Importance on Economic Growth of Oli-Producing Developing Countries (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this study is to examine and estimate the weight importance and effects of institutional factors on the economic growth of oil-producing developing countries considering the effect of the institution index on the economic growth of these countries. Investigation of the relative importance of these factors not only contributes to the identification of the effect of institutional factors on the economic growth of mentioned countries but also provides the field for institutional reforms by identifying the relative weight of each factor. Oil countries were identified in this research based on UNCTAD's division (2008). Considering the correlated nature of institutional factors that are influenced by the conditions of the countries, it is not possible to examine the relative importance of the effect of institutional factors on economic growth through regression methods. Accordingly, Johnson's Relative Weight Technique was used through SPSS programming. Estimation results showed that government effectiveness (GE), regulatory quality (RQ), and control of corruption (CoC) were the factors with the highest weight importance among other institutional factors regarding their effects on the economic growth of oil-producing developing countries. Furthermore, the institution index was calculated after identifying weigh the importance of institutional factors in the weighted average of these factors. Then, the effects of institutions on economic growth were estimated based on the dynamic panel data (GMM) and Dawson Model. Results proved the effect of the institution index on economic growth.